2004
DOI: 10.1065/lca2004.10.188
|View full text |Cite
|
Sign up to set email alerts
|

Scenario Modelling in Prospective LCA of Transport Systems. Application of Formative Scenario Analysis (11 pp)

Abstract: depth analysis of the future development of each single unit process, while still accounting for the requirements of the final scenario integration. Due to its high transparency, the procedure supports the validation of LCI results. Furthermore, it is wellsuited for incorporation into participatory methods so as to increase their credibility. Outlook and Future Work. Thus far, the proposed approach is only applied on a vehicle level not taking into account alterations in demand and use of different transport m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 21 publications
0
61
0
2
Order By: Relevance
“…One possibility is, for instance, utilizing the results in scenario analysis, which is a frequently used approach in transition management [5,7,10]. Thereby, the identified impact factors can be utilized for formative scenario construction [20,61]; in addition, the provided overall vision can be used for intuitive scenario definition. Further, the relevance judgments of the impact factors regarding both short-and long-term perspectives offer first evidence on the temporal dynamics and help in considering different planning horizons.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is, for instance, utilizing the results in scenario analysis, which is a frequently used approach in transition management [5,7,10]. Thereby, the identified impact factors can be utilized for formative scenario construction [20,61]; in addition, the provided overall vision can be used for intuitive scenario definition. Further, the relevance judgments of the impact factors regarding both short-and long-term perspectives offer first evidence on the temporal dynamics and help in considering different planning horizons.…”
Section: Discussionmentioning
confidence: 99%
“…[51]). Recent studies have shown the potential of combining LCA with other methods, such as life cycle costing [52] or formative scenario analysis [53].…”
Section: Characteristics Of the Selected Methodsmentioning
confidence: 99%
“…For policy development, we need to analyse all possible direct and indirect consequences of potential policy options using life cycle-based scenario analysis for which CLCA, BLCSA, FLCSA and other scenariobased life cycle approaches (e.g. Spielmann et al 2005 ;Hertwich et al 2014 ;Koning et al 2015 ) are best suited. For monitoring existing, accepted policies, we need clear black and white answers and no scenario-based ranges of answers; for this, ALCA seems better suited.…”
Section: Discussionmentioning
confidence: 99%